Physical & Chemical properties of Pulverised Fuel Ash - Khairul Nizar, Ismail, Dr.; Kamarudin, Hussin, Kol. Prof. Dato' Dr.; Mohd Sobri, Idris (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.